A Sertoli-Leydig ovarian tumor presenting as ovarian torsion: A case report - Samia Tligui; Hounaida Mahfoud; Samia Sassi; Hanane Inrhaoun; Najat Lamalmi; Fatima El Hassouni; Samir Bargach (Elsevier, 2024)
Torsion occurs as a complication in 10% of cases of ovarian tumors. It predominantly occurs in benign ones, while malignant tumors are less prone to torsion. Sertoli-Leydig cell tumors are highly unusual sex cord-stromal tumors of the ovary, accounting for less than 0.2% of all ovarian cancers.A 39-year-old patient presented to the emergency department with a Sertoli-Leydig cell tumor diagnosed due to ovarian torsion. The clinical presentation was characterized by abdominal pain. Ultrasound indicated signs of torsion, and torsion of the right ovary was subsequently confirmed during laparotomy. A salpingo-oophorectomy was performed, and histological examination revealed a moderately differentiated Sertoli-Leydig cell tumor.Sertoli-Leydig cell tumors often present with hormone-related or non-hormonal symptoms. Surgery plays a crucial role in both diagnosis and treatment. Postoperative treatment is not necessary for well-differentiated Sertoli-Leydig cell tumors in stage IA-IB. However, patients with grade 2-3 disease, advanced stage, or heterologous elements may consider adjuvant treatment.As these tumors are rare, this case contributes to the documentation of Sertoli-Leydig cell tumors, with a case diagnosed due to ovarian torsion. The case highlights the importance of establishing international registries of Sertoli-Leydig cell tumor cases for standardized management.